PENGARUH PENGGUNAAN MODUL AJAR IPA TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 1 HILIDUHO - Lahagu, Jelinus; Gulo, Hardikupatu; Waruwu, Toroziduhu; Zega, Novelina Andriani (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
This research is motivated by the low achievement of science learning outcomes of students at SMP Negeri 1 Hiliduho, which is still below the Minimum Completion Criteria due to the limited variety of learning resources and the dominance of conventional learning methods. This study aims to analyze the influence and effectiveness of the use of science teaching modules in improving students' cognitive competence. The method applied is quantitative with a pre-experimental one-group pretest-posttest design, where the research sample was determined through a purposive sampling technique among eighth-grade students. The data collection instrument used an objective test whose validity and reliability have been tested. The research findings show a statistically significant increase, evidenced by the Paired Sample t-test hypothesis test which produced a Sig. (2-tailed) value of 0.000 < 0.05. In addition, there was an increase in the average score from 59.33 (pre-test) to 76.67 (post-test) with a jump in classical completeness from 3.3% to 80%. Effectiveness analysis using the N-Gain test showed an average score of 0.4202, which is in the moderate category (0.30 ? g < 0.70). The main conclusion of this study confirms that the implementation of science teaching modules has a significant positive impact and is proven effective in improving student learning outcomes. Therefore, it is recommended as a supporting teaching material to optimize the understanding of science concepts in schools. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya capaian hasil belajar IPA siswa di SMP Negeri 1 Hiliduho yang masih berada di bawah Kriteria Ketuntasan Minimal akibat minimnya variasi sumber belajar dan dominasi metode pembelajaran konvensional. Penelitian ini bertujuan untuk menganalisis pengaruh serta tingkat efektivitas penggunaan modul ajar IPA dalam meningkatkan kompetensi kognitif siswa. Metode yang diterapkan adalah kuantitatif dengan desain pre-experimental one-group pretest-posttest , di mana sampel penelitian ditentukan melalui teknik purposive sampling pada siswa kelas VIII. Instrumen pengumpulan data menggunakan tes objektif yang telah teruji validitas dan reliabilitasnya. Temuan penelitian menunjukkan adanya peningkatan signifikan secara statistik, dibuktikan dengan uji hipotesis Paired Sample t-test yang menghasilkan nilai Sig. (2-tailed) sebesar 0,000 < 0,05. Selain itu, terjadi kenaikan rata-rata nilai dari 59,33 (pre-test) menjadi 76,67 (post-test) dengan lonjakan ketuntasan klasikal dari 3,3% menjadi 80%. Analisis efektivitas menggunakan uji N-Gain menunjukkan skor rata-rata 0,4202 yang berada pada kategori sedang (0,30 ? g < 0,70). Simpulan utama penelitian ini menegaskan bahwa implementasi modul ajar IPA memiliki pengaruh positif yang signifikan dan terbukti efektif dalam memperbaiki hasil belajar siswa, sehingga direkomendasikan sebagai bahan ajar pendukung untuk mengoptimalkan pemahaman konsep sains di sekolah.